QUALITY OF LIFE IN PEOPLE WITH VENOUS ULCERS AND THE CHARACTERISTICS AND SYMPTOMS ASSOCIATED WITH THE WOUND (Estima – Brazilian Journal of Enterostomal Therapy, 2021)
Objective: to evaluate the quality of life of people with venous ulcers and correlate with the clinical characteristics and symptoms associated with the wound. Method: quantitative, cross-sectional and analytical study. For analyzes of associations of qualitative variables, the Chi-square and Fisher’s exact tests were applied, and for quantitative variables, Spearman’s correlation coefficient. The Pressure Ulcer Scale for Healing instrument was used to assess the wound and the Freiburg Life Quality Assessment Wound-wk for quality of life analysis. The study included 103 subjects with a wound time of more than six weeks, of venous etiology. Results: there was a correlation between the clinical characteristics of the venous ulcer and symptoms associated with quality of life. In the physical symptoms dimensions, people with venous ulcers had a worse score in relation to the pain symptom (p